Penyuluhan Kesehatan Manajemen Nyeri Pada Warga Dawis Cempaka Kelurahan Mojosongo Surakarta - Rahayu Setyaningsih; Aprilia Nuryanti; Undari Nurkalis (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
Pain that arises experience by the body will have an unpleasant impact on those who experience it. Not many people are able to cope with pain well, causing new problem such as not being able to fulfill their daily needs, not being able to move well. Most people to deal with pain take painkillers, rarely use alternative actions other than pharmacological measures (taking medicine) as well as the residents of Dawis Cempaka, Mojosongo Village, almost most of those who experience pain will overcome it by taking medicine. Knowledge about pain management is still lacking apart from pharmalogical therapy, the absence of health adres and the low utilization of posyandu for the elderly or perhaps not yet established in the area problems that will be overcome in this community service activity. The solution offered is health education about pain management so that Dawis Cempaka residents increase their knowledge and are able to take advantage of existing health facilities. The activity will be carried out with a pretest to detemine the level of knowledge before health education is carried out, after that it is continued with the provision of material on pain management, will be given a post test to determine the increase knowledge.